One-dimensional nanostructures : principles and applications - Zhai, Tianyou, 1980-; Yao, Jiannian, 1953- (Hoboken, N.J. : Wiley, 2012)
"This book consolidates a wealth of current and complex information regarding one-dimensional nanostructures into one volume for practicing chemists, physicists, materials scientists, and engineers in industry and academia. One-dimensional nanostructures are not only in the forefront of the hottest fundamental materials research, but they are also becoming part of our daily lives. 69 experts from around the world provide in-depth chapters on their specific areas of expertise, coving all important applications such as: photodetectors, gas sensors, biosensors, chemical sensors, field-emitters, lasers, lithium-ion batteries, supercapacitors, light emitting diodes (LED), photovoltaics, nanogenerators, thermoelectrics, piezoelectrics and field-effect transistors"--
Chapter 9: Doping Effect on Novel Optical Properties of Semiconductor Nanowires9.1 Introduction; 9.2 Results and Discussion; 9.3 Conclusion and Outlook; Acknowledgment; References; Chapter 10: Quantum Confinement Phenomena in Bioinspired and Biological Peptide Nanostructures; 10.1 Introduction; 10.2 Bioinspired Peptide Nanostructures; 10.3 Peptide Nanostructured Materials (PNM): Intrinsic Basic Physics; 10.4 Experimental Techniques With Peptide Nanotubes (PNTs); 10.5 Quantum Confinement In PNM Structures; 10.6 Conclusions; Acknowledgment; References
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Nanowires; Semiconductors -- Materials; One-dimensional conductors; Nanostructured materials; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Nanostructured materials; Nanowires; One-dimensional conductors; Semiconductors -- Materials; Electronic books; Electronic books